Assembleia de ácaros edáficos em sistemas de produção agropecuário no norte de Mato Grosso - Ferreira, Cleber Brandino (2023)
Mites are arachnid that play fundamental ecological roles such as decomposition of organic material and natural pest control. They are found in different habitats, including different agricultural production systems. Despite being widely disseminated, information about its biodiversity in production systems is still incipient. In this context, we identified and quantified the edaphic mites species in production systems. The samples were carried out in Sinop, in the northern region of the state of Mato Grosso. The evaluated systems were: (1) soybean-corn succession (SCS) cultivating soybean in the summer and corn intercropped with brachiaria in the second season (2) crop, livestock and forest integration system (ILPF) containing triple rows of eucalyptus distant 30 meters from each other with soybean cultivation in the summer followed by corn intercropped with Brachiaria for beef cattle grazing after corn harvesting and, (3) Secondary forest. Richness and Abundance was higher Secondary forest in contrast to soybean-corn succession and crop-levestock-forest systems. Oribatids and Sarcoptiformes were the most abundant Orders in all sampled habitats. In Gamasina, Multidentorhodacarus squamosus (Karg 2000) (Rhodacaridae) was the more abundant species in all habitats, being more collected in the SCS system compared to the ILPF. Production systems directly influenced the richness and quantity of edaphic mite species.